INTERCULTURAL SKILLS IN HIGHER EDUCATION: A SYSTEMATIC MAPPING - Salles, Fabiane Aparecida Santos Clemente (2024)
With the polysemy and conceptual abstraction of intercultural competencies, more and more studies are developing in the area in search of empirical directions. This research had the general objective of analyzing how intercultural competencies (IC) are developed in higher education based on a systematic mapping (MS) of the literature. Through a MS research protocol, we also sought to verify the main intercultural competencies in this context. The results point to an increase in the number of scientific publications on the construct after 2015, also allowing us to map the most adopted models. Intercultural competence is developed through several joint actions within the scope of higher education, such as teacher training, curriculum restructuring, institutionalized projects and actions, and the internationalization process stands out as one of the main means for this. Intercultural competencies are mostly based on the models or instruments adopted in each research. As a result, there was also a lack of studies that target teachers, as well as a low number of studies in Latin America.